THE HOLY WARRIORS IN THE FRESCO PAINTING OF KOSOVO AND METOHIJA AS MODELS OF THE PUPPETS OF THE KOSOVO COVENANT - Миловановић, Ана (Political Review, 2025)
The paper studies the holy warriors in the fresco painting of Kosovo and Metohija as a model for the creation of the puppets of the Kosovo Covenant. The aim of the paper is to present frescoes of Kosovo and Metohija as an optimal inspiration for the creation of the puppets of the Kosovo Covenant. The pattern of the research was the warrior puppets of preschool teacher students of the Faculty of Education in Belgrade, created at the course Drama and Movement. The following methods were used: descriptive, analysis of content, and comparison. The reasons for choosing holy warriors as role models are presented: holiness as the central state-building idea of the Serbs and the uniqueness of Serbian warriors in the Middle Ages; the heroes of the Kosovo Covenant as exemplary holy warriors among the Serbs; the exceptional artistic value of holy warriors on frescoes of Kosovo and Metohija. The universal principles of puppet creation and special principles used in the creation of puppets of the Kosovo Covenant were exposed. There were examples of the puppets created by the model of the holy warriors in the fresco painting of Kosovo and Metohija. It was concluded that the students successfully found their own stylistic procedures in the creation of the puppets of the Kosovo Covenant.